2022
DOI: 10.3390/s22134724
|View full text |Cite
|
Sign up to set email alerts
|

The Validity of the Push Band 2.0 on the Reactive Strength Index Assessment in Drop Jump

Abstract: This study aims to verify the validity of the Push Band 2.0 (PB2.0) device on the reactive strength index (RSI) measurement, using a force plate (FP) and an optical sensor device, OptoJump (OPT), as a reference. Twenty trained athletes performed 60 drop jump trials with a height box of 30 cm. A randomized repeated measures study was conducted during a single session using the PB2.0, the OPT, and the plate force manually synchronized to obtain RSI data for each jump. Validity was analyzed by contrasting three m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…The study followed the same procedures outlined in previous research related to the validation and intra-session reliability of jumps assessment equipment ( Montoro-Bombú et al, 2022 ). All participants performed three DJ (for RSI assessment), with jump parameters recorded simultaneously with an FP and the IMU measurement device.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The study followed the same procedures outlined in previous research related to the validation and intra-session reliability of jumps assessment equipment ( Montoro-Bombú et al, 2022 ). All participants performed three DJ (for RSI assessment), with jump parameters recorded simultaneously with an FP and the IMU measurement device.…”
Section: Methodsmentioning
confidence: 99%
“…Studies have demonstrated the validity and reliability of different accelerometer devices for velocity-based training ( Balsalobre-Fernandez et al, 2016 ; Hughes et al, 2019 ; Lake et al, 2019 ), injury detection ( Li et al, 2016 ), and monitoring sleep quality ( Reimers et al, 2021 ) with high accuracy. Additionally, separate investigations have involved the validation of the functionality of these devices for the measurement of jump metrics ( Choukou et al, 2014 ; Lake et al, 2018 ; Montalvo et al, 2021 ; Montoro-Bombú et al, 2022 ). A new commercially available inertial measurement unit (IMU), namely the Output Sport measurement device, has been used for fatigue assessment ( Buckley et al, 2017 ), injury prevention ( Whelan et al, 2016 ), agility ( Johnston et al, 2019 ), velocity-based training ( O'Reilly et al, 2015 ), lower limb exercise assessments ( O'Reilly et al, 2017a ; O'Reilly et al, 2017b ; O'Reilly et al, 2018 ), and postural control and balance evaluations ( Johnston et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ideally, athletes should maximize JH while minimizing ground contact time. The RSI (Young, 1995) is the proposed metric that solves these problems through the use of different devices that can be easily apply during training (Montoro-Bombú et al, 2022). So far, we have not found in the literature any study assuming that the RSI can be considered a plyometric intensity variable.…”
Section: General Discussion On Plyometric Intensitymentioning
confidence: 99%
“…(Lees and Fahmi, 1994b), A was the first to refute all previous FH criteria and contributions (Komi and Bosco, 1978b;Bobbert et al, 1987b), indicating that the best performance for a net increase in JH, instantaneous power, and other parameters occurred at 12 cm FH. There have been considerable contributions regarding the best conditions for power production (Pw) (Bosco et al, 1983b;Matic et al, 2015b;Morin et al, 2019), ground reaction forces (GRF), rate of force development (RFD) (Jensen and Ebben, 2007;Ebben et al, 2008;Kossow and Ebben, 2018a), and the reactive strength index (RSI), as well as the differences between CMJ and DJ (Young, 1995;Young et al, 1995;Struzik et al, 2016;Montoro-Bombú et al, 2022), although not always consistent. The emergence of these variables has led to the utilization of different criteria for assuming plyometric training intensity.…”
Section: Introductionmentioning
confidence: 99%